Modified resin and preparation method thereof, and ethylene glycol impurity removal method
Patent Information
- Application Number
- CN202410556988.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-07
AI Technical Summary
[0004]本发明所要解决的技术问题是树脂吸附法中化学吸附对乙二醇紫外透光率的提升效果不明显、物理吸附存在杂质残留和解吸问题,本发明提供一种改性树脂及其制备方法、乙二醇除杂方法
[0017] The modified resin provided in this application is used for impurity removal from ethylene glycol. The modified resin contains a composite resin, which contains sulfonic acid groups (-SO3H). The modifier is grafted onto the composite resin and contains -OH groups. The sulfonic acid groups H in the modified resin... + Under catalysis, aldehydes and carboxylic acid impurities in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, removing these impurities from the ethylene glycol. The mesoporous molecular sieve is uniformly present in the composite resin. When aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions to generate water, the mesoporous molecular sieve rapidly adsorbs the generated water, significantly reducing the reverse reaction caused by water accumulation. This effectively prevents impurity desorption and significantly improves the UV transmittance of ethylene glycol (using the modified resin of this application to remove impurities from ethylene glycol can increase the UV transmittance of ethylene glycol at 220 nm by over 40%).
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ethylene glycol refining technology, specifically relating to a modified resin and its preparation method, and a method for removing impurities from ethylene glycol. Background Technology
[0002] Ethylene glycol, an important petrochemical product, is a crucial raw material for plasticizers and refrigerants; its primary application is currently in polyester production. When used as a polyester raw material, it must meet all the specifications for polyester-grade products in the national standard GB / T 4649—2018. Among these, ultraviolet (UV) transmittance and color directly affect the quality of polyester products. The UV transmittance of ethylene glycol is influenced by impurities. According to existing literature, the main impurities affecting UV transmittance in ethylene glycol are ketones, aldehydes, esters, carboxylic acids and their derivatives containing C=O, as well as unsaturated organic compounds containing C=C. Most of these substances significantly impact UV transmittance at 220 nm and 275 nm, making it difficult to improve transmittance at these wavelengths. Other ethers and alcohols also affect UV transmittance.
[0003] To improve the transmittance of ethylene glycol, various impurities need to be removed, primarily through physical adsorption and chemical conversion methods. Chemical conversion methods include catalytic hydrogenation, sodium bisulfite aldehyde removal, sodium borohydride reduction, and aldol condensation. For ethylene glycol with a wide variety of impurities, chemical conversion is relatively complex and costly. Physical adsorption methods, depending on the adsorbent and adsorption principle, are further subdivided into activated carbon adsorption and resin adsorption. While activated carbon adsorption can improve the UV transmittance of ethylene glycol, its limited adsorption capacity leads to decreased efficiency after a period of use, and activated carbon is difficult to regenerate completely, resulting in high operating costs. Resins are commonly used adsorbents in ethylene glycol purification. Based on the impurity adsorption principle, they can be divided into chemical adsorption and physical adsorption. Chemical adsorption relies on the functional groups of the resin as catalysts. Ethylene glycol reacts with impurities to form substances that do not affect UV transmittance, or the anions and cations in the resin react with impurities in ethylene glycol to produce impurities insoluble in EG, which are then separated and purified through subsequent filtration. According to existing literature, the above methods have little effect on improving the UV transmittance of ethylene glycol (at 220 nm, the improvement in UV transmittance is mostly less than 10%), and most resins can only adsorb certain specific impurities, with limited adsorption capacity for other impurities in ethylene glycol. Physical adsorption mainly relies on van der Waals forces and hydrogen bonds formed between the resin's own structure and impurities, and can adsorb a wide variety of impurities. However, due to the instability of the van der Waals forces and hydrogen bonds, there are problems with impurity residue and desorption. Summary of the Invention
[0004] The technical problem to be solved by the present invention is that the effect of chemical adsorption on improving the ultraviolet transmittance of ethylene glycol in the resin adsorption method is not obvious, and physical adsorption has the problems of impurity residue and desorption. The present invention provides a modified resin and its preparation method, and a method for removing impurities from ethylene glycol.
[0005] To solve the above-mentioned technical problems, the present invention provides a modified resin for ethylene glycol purification, comprising a composite resin and a modifier grafted onto the composite resin, wherein the modifier comprises an alkanolamine organic compound, and the composite resin contains sulfonic acid groups and mesoporous molecular sieves.
[0006] Preferably, the alkanolamine organic compound comprises one or more of the following structural formulas: Where 1≤n≤4, R1 is selected from -CH3 or -CH2-CH3.
[0007] Secondly, this application provides a method for preparing a modified resin, comprising the following steps: A composite resin containing sulfonic acid groups and mesoporous molecular sieves was obtained; The composite resin is mixed with an alcohol amine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups.
[0008] Preferably, obtaining a composite resin containing sulfonic acid groups and mesoporous molecular sieves includes the following steps: A resin containing sulfonic acid groups is mixed with a mesoporous molecular sieve to form a melt blend, and the melt blend is pretreated to obtain the composite resin.
[0009] Preferably, the total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 17.6% to 20.27%. The mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve is (10~100):1.
[0010] Preferably, the total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 19% to 20.27%.
[0011] Preferably, the process of mixing a resin containing sulfonic acid groups with a mesoporous molecular sieve to form a melt blend includes the following steps: The resin containing sulfonic acid groups and the mesoporous molecular sieve are added to a container and premixed by stirring, followed by melt mixing. The melt mixing temperature is 160~230℃ and the stirring time is ≥2h.
[0012] Preferably, the composite resin is obtained by pretreating the melt blend, including the following steps: The molten blend is compressed into tablets and cooled to obtain a composite resin. The preheating time of the press used for tableting is 10~30min, the pressure of tableting is 0.5~3.0MPa, and the melt compression temperature during tableting is 160~220℃. The D50 particle size of the composite resin is 0.5~1.5mm.
[0013] Preferably, the melt compression temperature in the tableting process is 180~220℃.
[0014] Preferably, the composite resin is mixed with an alkanolamine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups, comprising the following steps: A composite resin and an alcohol amine organic compound with a mass ratio of (4.1~8.2):1 are added to a container, heated and stirred at a temperature of 60~100℃ for ≥4h. After that, the mixture is filtered, washed with water, and dried to obtain a modified resin containing -OH and -SO3H groups.
[0015] Thirdly, this application provides a method for removing impurities from ethylene glycol, including the modified resin described above or the modified resin prepared by the method described above. The ethylene glycol impurity removal method includes the following steps: The modified resin is then post-treated. The post-treatment includes washing the modified resin with an alcohol solution; The post-treated modified resin was packed into a column, and impurities were removed by passing it through the column with ethylene glycol.
[0016] Preferably, the modified resin is post-treated, including the following steps: The modified resin and pure water are mixed to obtain a first solution. The first solution is stirred and washed for the first time. The pure water is replaced during the first stirring and washing process. The first stirring and washing is completed when the first solution is colorless and transparent and has a conductivity of <10μs / cm. The amount of pure water added is 2 to 3 times the volume of the modified resin, and the first stirring and washing time is 0.5 to 4 hours. The pure water is replaced when the transmittance of the first solution at 220 nm does not decrease. After the first stirring and cleaning is completed, the modified resin is washed with an alcohol solution, including the following steps: mixing the modified resin and the first alcohol solution to obtain a second solution, stirring and cleaning the second solution a second time, replacing the first alcohol solution during the second stirring and cleaning process, and stirring and cleaning the second solution until the transmittance of the second solution at 220 nm is >10%, at which point the second stirring and cleaning is completed. The amount of the first alcohol solution added is 2 to 3 times the volume of the modified resin, and the second stirring and washing time is 2 to 4 hours. The first alcohol solution is replaced when the transmittance of the second solution at 220 nm does not decrease. The modified resin after post-treatment is packed into a column, and the ethylene glycol column impurity removal includes the following steps: after the second stirring and washing, the modified resin after the second stirring and washing is transferred to the adsorption column, and the second alcohol solution is continuously passed through the adsorption column dynamically until the transmittance of the second alcohol solution at 220 nm is higher than 50%, and the modified resin is dried.
[0017] The modified resin provided in this application is used for impurity removal from ethylene glycol. The modified resin contains a composite resin, which contains sulfonic acid groups (-SO3H). The modifier is grafted onto the composite resin and contains -OH groups. The sulfonic acid groups H in the modified resin... + Under catalysis, aldehydes and carboxylic acid impurities in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, removing these impurities from the ethylene glycol. The mesoporous molecular sieve is uniformly present in the composite resin. When aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions to generate water, the mesoporous molecular sieve rapidly adsorbs the generated water, significantly reducing the reverse reaction caused by water accumulation. This effectively prevents impurity desorption and significantly improves the UV transmittance of ethylene glycol (using the modified resin of this application to remove impurities from ethylene glycol can increase the UV transmittance of ethylene glycol at 220 nm by over 40%). Detailed Implementation
[0018] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0019] In a first aspect, embodiments of this application provide a modified resin for ethylene glycol impurity removal, comprising a composite resin and a modifier grafted onto the composite resin, the modifier comprising an alkanolamine organic compound, and the composite resin containing sulfonic acid groups and mesoporous molecular sieves.
[0020] The modified resin provided in this application is used for impurity removal from ethylene glycol. The modified resin contains a composite resin, which contains sulfonic acid groups (-SO3H). The modifier is grafted onto the composite resin and contains -OH groups. The sulfonic acid groups H in the modified resin... +Under catalysis, aldehydes and carboxylic acid impurities in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, removing these impurities from the ethylene glycol. (After adsorption by the modified resin, the UV transmittance of ethylene glycol at 220 nm can be increased by over 40%).
[0021] The composite resin contains mesoporous molecular sieves.
[0022] Specifically, the mesoporous molecular sieve is uniformly present in the composite resin. When aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions to generate water, the mesoporous molecular sieve rapidly adsorbs the generated water, significantly reducing the reverse reaction caused by water accumulation, effectively avoiding impurity desorption, and significantly improving the ultraviolet transmittance of ethylene glycol (using the modified resin of this application to remove impurities from ethylene glycol can improve the ultraviolet transmittance of ethylene glycol at 220 nm by more than 40%).
[0023] In some embodiments, the alkanolamine organic compound comprises one or more of the following structural formulas: Where 1≤n≤4, R1 is selected from -CH3 or -CH2-CH3.
[0024] Specifically, 1 ≤ n ≤ 4, where n is an integer and can be 1, 2, 3, or 4. In structural formulas 2 and 3, R1 is selected from the -CH3 group, or R1 is selected from the -CH2-CH3 group.
[0025] Secondly, this application provides a method for preparing the modified resin described above, comprising the following steps: A composite resin containing sulfonic acid groups and mesoporous molecular sieves is obtained; the composite resin is mixed with an alkanolamine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups.
[0026] The modified resin preparation method provided in this application obtains a composite resin containing sulfonic acid groups and mesoporous molecular sieves. After modification with an appropriate amount of an alkanolamine organic modifier, a modified resin containing -OH and -SO3H groups is obtained. In the modified resin, the sulfonic acid groups H... + Under catalysis, aldehydes and carboxylic acid impurities in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, removing these impurities from the ethylene glycol. Mesoporous molecular sieves can uniformly exist within the composite and modified resin structures. When aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions to generate water, the mesoporous molecular sieves rapidly adsorb the generated water, significantly reducing the reverse reaction caused by water accumulation, effectively preventing impurity desorption, and significantly improving the UV transmittance of ethylene glycol.
[0027] In some embodiments, obtaining a composite resin containing sulfonic acid groups and molecular sieves includes the following steps: A resin containing sulfonic acid groups is mixed with a mesoporous molecular sieve to form a melt blend, and the melt blend is pretreated to obtain the composite resin.
[0028] Specifically, a resin containing sulfonic acid groups is mixed with a mesoporous molecular sieve to form a melt blend. The mesoporous molecular sieve can be uniformly present in the composite resin and modified resin structure. When aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions to generate water, the mesoporous molecular sieve can quickly adsorb the generated water, significantly reducing the reverse reaction caused by water accumulation, effectively avoiding the desorption of impurities, and significantly improving the ultraviolet transmittance of ethylene glycol (the modified resin adsorbing ethylene glycol provided in this application, in its best embodiment, can improve the ultraviolet transmittance of ethylene glycol at 220 nm by more than 40%).
[0029] In some embodiments, the total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 17.6% to 20.27%.
[0030] Specifically, when the sulfonic acid groups in the resin exceed 20.27%, the mechanical properties of the composite resin deteriorate. When the sulfonic acid groups are below 17.6%, fewer alkanolamine organic compounds are introduced into the resin, affecting the subsequent impurity adsorption effect. Within the range of 17.6% to 20.27% sulfonic acid groups in the resin, the composite resin exhibits high mechanical strength and is also conducive to the introduction of alkanolamine organic compounds, improving the impurity removal effect of ethylene glycol. Specifically, the mass content of sulfonic acid groups in the resin can be 17.6%, 18.0%, 18.3%, 18.5%, 18.8%, 19.0%, 19.2%, 19.5%, 19.7%, 19.8%, 20.0%, 20.1%, 20.2%, or 20.27%, as long as the sulfonic acid groups in the resin are within the range of 17.6% to 20.27%.
[0031] In some preferred embodiments, the total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 19% to 20.27%.
[0032] Specifically, the mass content of sulfonic acid groups in the resin is in the range of 19% to 20.27%. The composite resin has higher mechanical strength and is more conducive to the introduction of alkanolamine organic compounds. The modified resin has a high -OH content, which is conducive to the rapid removal of aldehydes and carboxylic acids from ethylene glycol.
[0033] In some embodiments, the mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve is (10~100):1.
[0034] Specifically, introducing mesoporous molecular sieves into a resin containing sulfonic acid groups, with a mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve in the range of (10~100):1, allows the mesoporous molecular sieve to rapidly adsorb the water generated during aldol condensation and esterification reactions of aldehydes and carboxylic acids in ethylene glycol. This significantly reduces the reverse reaction caused by water accumulation, effectively preventing impurity desorption and significantly improving the transmittance of ethylene glycol. If the mass ratio is higher than 100:1, the amount of mesoporous molecular sieve introduced is too small, resulting in poor adsorption of product water by the resin and poor inhibition of the reverse reaction. If the mass ratio is lower than 10:1, the amount of alkanolamine organic matter introduced into the composite resin is small, leading to poor adsorption of aldehyde and carboxylic acid impurities.
[0035] Specifically, the mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve can be in the range of (100~90):1, (90~80):1, (80~70):1, (70~60):1, (50~60):1, (40~50):1, (30~40):1, (20~30):1, (10~20):1, etc., as long as the mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve is within the range of (10~100):1.
[0036] In some embodiments, mixing a resin containing sulfonic acid groups with a mesoporous molecular sieve to form a melt blend includes the following steps: The resin containing sulfonic acid groups and the mesoporous molecular sieve are added to a container and premixed by stirring, followed by melt mixing. The melt mixing temperature is 160℃~230℃ and the stirring time is ≥2h.
[0037] Specifically, a melt mixing temperature within the range of 160℃ to 230℃ and a stirring time greater than 2 hours are beneficial for uniformly introducing mesoporous molecular sieves into the resin containing sulfonic acid groups, and for ensuring that the molecular sieves are evenly distributed within the resin containing sulfonic acid groups. This improves the uniformity, stability, and mechanical strength of the composite resin. If the melt mixing temperature is below 160℃, the interaction between the mesoporous molecular sieves and the resin containing sulfonic acid groups is weak, resulting in an unstable composite resin; if the temperature is above 230℃, the mechanical strength of the composite resin deteriorates.
[0038] In some preferred embodiments, the melting and mixing temperature is 180°C to 220°C.
[0039] Specifically, when the melting and mixing temperature is in the range of 180℃ to 220℃, the interaction between the mesoporous molecular sieve and the resin containing sulfonic acid groups is strong, the mesoporous molecular sieve is uniformly distributed in the resin containing sulfonic acid groups, the composite resin has high mechanical strength, and the impurity removal efficiency is improved.
[0040] In some embodiments, pretreatment of the melt blend to obtain a composite resin includes the following steps: The molten blend is compressed into tablets and cooled to obtain a composite resin. The preheating time of the press used for tableting is 10~30min, the pressure of tableting is 0.5~3.0MPa, and the melt compression temperature during tableting is 160~220℃. The D50 particle size of the composite resin is 0.5~1.5mm.
[0041] Specifically, compressing the melt blend into tablets yields a composite resin with a particle size D50 of 0.5–1.5 mm. This helps improve the adsorption effect of the modified resin on macromolecular impurities in ethylene glycol, reduces the probability of interaction between impurities and hydroxyl groups in the modified resin, and enhances the adsorption effect on impurities in ethylene glycol. If the particle size D50 is less than 0.5 mm, the adsorption effect of the modified resin on macromolecular impurities will be poor; if the particle size D50 is greater than 1.5 mm, the probability of interaction between impurities and hydroxyl groups in the modified resin will be reduced, affecting the impurity adsorption effect. Specifically, the D50 particle size of the composite resin can be in the ranges of 0.5 mm–0.8 mm, 0.8 mm–1.0 mm, 1.0 mm–1.3 mm, and 1.3 mm–1.5 mm.
[0042] The melt compression temperature in tableting is 160~220℃. The melt compression temperature should be above the melting temperature of the resin containing sulfonic acid groups, which is beneficial for tableting the resin.
[0043] In some preferred embodiments, the melt compression temperature during tableting is 180~200°C.
[0044] A melt compression temperature in the range of 180~200℃ helps to improve compression efficiency.
[0045] The melt compression temperature in the tableting process is 180~220℃.
[0046] In some embodiments, the composite resin is mixed with an alkanolamine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups, comprising the following steps: A composite resin and an alcohol amine organic compound with a mass ratio of (4.1~8.2):1 are added to a container, heated and stirred at a temperature of 60~100℃ for ≥4h. After that, the mixture is filtered, washed with water, and dried to obtain a modified resin containing -OH and -SO3H groups.
[0047] Specifically, the mass ratio of composite resin to alkanolamine organic compound is in the range of (4.1~8.2):1. After the composite resin is modified with an appropriate amount of alkanolamine, a modified resin containing -OH and -SO3H groups is obtained; in the modified resin, sulfonic acid groups H... +Under catalysis, aldehydes and carboxylic acids in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, removing these impurities. If the mass ratio of the composite resin to alkanolamine organic compounds is less than 4.1, the grafting amount of alkanolamine is too high, leading to an increase in H+ in the resin. + The content of aldol condensation and esterification reactions is relatively low when adsorbing impurities, and the adsorption effect on impurities is generally poor. If the mass ratio of composite resin to alkanolamine organic matter is higher than 8.2, the content of alkanolamine organic matter is low, the amount of alkanolamine grafting is small, and the adsorption effect on impurities is generally poor.
[0048] Heating temperature in the range of 60~100℃ and stirring time ≥4h are beneficial for grafting alcoholic amine organic compounds onto composite resins.
[0049] It should be noted that resins containing sulfonic acid groups need to be introduced into mesoporous molecular sieves to prepare composite resins before grafting alkanolamine organic compounds. If resins containing sulfonic acid groups are grafted with alkanolamine organic compounds first and then introduced into mesoporous molecular sieves, the free hydroxyl groups in the mesoporous molecular sieves will affect the amount of alkanolamine organic compounds introduced, reducing the adsorption effect on subsequent impurities.
[0050] Thirdly, this application provides a method for removing impurities from ethylene glycol, including the modified resin described above or the modified resin prepared by the method described above. The ethylene glycol impurity removal method includes the following steps: The modified resin is then post-treated. The post-treatment includes washing the modified resin with an alcohol solution; The post-treated modified resin was packed into a column, and impurities were removed by passing it through the column with ethylene glycol.
[0051] In the ethylene glycol impurity removal method provided in this application, the modified resin prepared in this application is first post-treated to remove organic impurities introduced during the production process of the modified resin. Then, the post-treated modified resin is used to remove impurities from ethylene glycol, which can effectively improve the ultraviolet transmittance of ethylene glycol and improve the impurity removal efficiency of ethylene glycol.
[0052] In some embodiments, the modified resin is post-treated, including the following steps: The modified resin and pure water are mixed to obtain a first solution. The first solution is then stirred and washed for the first time. During the first stirring and washing process, the pure water is replaced. The first stirring and washing is completed when the first solution is colorless and transparent and has a conductivity of <10μs / cm.
[0053] If the conductivity of the first solution is too high, it indicates a large amount of residual ions that dissolve in ethylene glycol, affecting the quality of ethylene glycol, such as its transmittance. The conductivity of the first solution should be limited to <10 μO / cm to remove residual small organic molecules from the modified resin and reduce residual ions in the resin.
[0054] It should be noted that the pure water is replaced during the first stirring and cleaning process, and this application does not limit the number of times the pure water is replaced.
[0055] In some embodiments, the amount of pure water added is 2 to 3 times the volume of the modified resin, and the first stirring and washing time is 0.5 to 4 hours; the pure water is replaced when the transmittance of the first solution at 220 nm does not decrease.
[0056] Specifically, the transmittance of the first solution did not decrease at 220 nm, indicating that the water absorption of impurities had reached saturation, and that there were relatively few water-soluble impurity ions remaining in the modified resin.
[0057] In some embodiments, after the first stirring and cleaning is completed, the modified resin is subjected to alcohol washing with an alcohol solution, including the following steps: mixing the modified resin and the first alcohol solution to obtain a second solution, performing a second stirring and cleaning on the second solution, replacing the first alcohol solution during the second stirring and cleaning, and ending the second stirring and cleaning when the transmittance of the second solution at 220 nm is >10%.
[0058] Specifically, the second stirring and washing process is terminated when the transmittance of the second solution at 220 nm exceeds 10%. This is to reduce resin washing time and conserve the amount of the first alcohol solution used. Continuing column washing with the second alcohol solution after the transmittance exceeds 10% consumes relatively less of the second alcohol solution. If mixing and stirring are performed throughout the process, impurities in the resin will be re-adsorbed after elution, resulting in incomplete resin washing. If column washing with alcohol solution is used throughout, there are more impurities in the early stages, leading to longer elution times and a larger consumption of alcohol solution.
[0059] In some embodiments, the amount of the first alcohol solution added is 2 to 3 times the volume of the modified resin, and the second stirring and washing time is 2 to 4 hours; the first alcohol solution is replaced when the transmittance of the second solution at 220 nm does not decrease.
[0060] Specifically, the transmittance of the second solution did not decrease at 220 nm, indicating that the absorption of impurities in the first alcohol solution had reached saturation, and that there were relatively few residual organic impurity ions in the modified resin.
[0061] In some embodiments, packing the post-treated modified resin into a column and removing impurities by passing it through the column with ethylene glycol includes the following steps: after the second stirring and washing is completed, the modified resin after the second stirring and washing is transferred to an adsorption column, and a second alcohol solution is continuously passed through the adsorption column dynamically until the transmittance of the second alcohol solution at 220 nm is higher than 50%, and the modified resin is dried.
[0062] Specifically, when the transmittance of the second alcohol solution after column chromatography is greater than 50% at 220 nm, it is close to the transmittance of the second alcohol solution before column chromatography. At this point, most of the impurities introduced by the resin during the production process are cleaned up and no longer cause significant pollution to the ethylene glycol.
[0063] Specifically, the modified resin is post-treated to prevent small organic molecules such as plasticizers and pore-forming agents contained in the modified resin from dissolving in ethylene glycol, affecting the light transmittance of ethylene glycol, and avoiding contamination of ethylene glycol by impurities inherent in the resin.
[0064] The first stirring and washing is to remove soluble impurities introduced into the modified resin during the original production process. The second stirring and washing is to remove organic impurities introduced into the modified resin during the original production process.
[0065] In some embodiments, the first alcohol solution includes at least one of a methanol solution and an ethanol solution; The second alcohol solution includes at least one of methanol solution and ethanol solution.
[0066] The present invention will be further illustrated by the following examples.
[0067] Specifically, this invention discloses the modified resin and its preparation method, as well as the ethylene glycol impurity removal method.
[0068] Example 1 Preparation of composite resin: 200g of resin containing sulfonic acid groups and 2g of mesoporous molecular sieve were added to a reactor and stirred for 2 minutes. The melt mixing temperature was set to 200℃, and the mixture was stirred thoroughly for 2 hours to form a melt blend, in which the mesoporous molecular sieve was fully embedded in the molten resin. The melt blend was then pressed into tablets and cooled to obtain a composite resin. The press preheating time was set to 20 minutes, the pressing pressure to 2.0 MPa, and the melt compression temperature during tableting to 200℃. The melt blend was processed into granules with a particle size D50 of 1.0 mm. After the process, the mixture was allowed to cool naturally to obtain the composite resin.
[0069] Among them, the resin containing sulfonic acid groups has a particle size D50 of 1.0 mm spherical particles, and the mass fraction of sulfonic acid groups in the resin is 19.0%.
[0070] Preparation of modified resin: 200 g of the above composite resin and 0.5 mol ethanolamine (30.9 g) were added to a reaction vessel and stirred continuously at 100 °C for 4 h. After the reaction was completed, the mixture was filtered, washed with water, and dried to obtain a modified resin with -OH and -SO3H groups on its surface.
[0071] Post-treatment of modified resins: A first solution was obtained by adding twice the volume of pure water to the modified resin. The first solution was then stirred and washed for the first time, with the pure water being replaced multiple times during the first stirring and washing process. The first solution was washed until it was colorless and transparent, and the conductivity of the washed solution was less than 10 μ0 / cm, in order to remove soluble impurities introduced into the resin during the original production process. The first stirring and washing time was 4 hours. The pure water was replaced when the transmittance of the first solution at 220 nm did not decrease.
[0072] After the first stirring and washing, the modified resin is washed with an alcohol solution, including the following steps: A second solution is obtained by adding a methanol solution with twice the resin volume to the modified resin; the second solution is then stirred and washed a second time, with the methanol solution being replaced during the second stirring and washing process. The second stirring and washing continues until the transmittance of the second solution at 220 nm is >10%, removing most of the organic impurities introduced during resin production. The second stirring and washing process is then complete. The second stirring and washing time is 4 hours. The methanol solution is replaced when the transmittance of the second solution at 220 nm does not decrease. After the second stirring and washing, the modified resin after the second stirring and washing was transferred to the adsorption column, and a methanol solution with a transmittance of more than 50% at 220 nm was continuously passed through the adsorption column until the transmittance of the second alcohol solution at 220 nm was higher than 50%, and then dried.
[0073] Ethylene glycol purification: The post-treated modified resin was packed into a column, and ethylene glycol was used for column adsorption to remove impurities.
[0074] After adsorption and impurity removal, the transmittance of ethylene glycol at all wavelengths increased. Among them, the ultraviolet transmittance at 220 nm, which is the most difficult to improve, reached 94%, with an average increase of more than 40% in ultraviolet transmittance; the ultraviolet transmittance at 250 nm was 95.80%, with an average increase of 19.05%; and the ultraviolet transmittance at 275 nm was 98.95%, with an average increase of 5.18%.
[0075] Table 1 shows the UV transmittance data of ethylene glycol before and after adsorption at different wavelengths in Example 1.
[0076] Table 1 Example 2 The difference between Example 2 and Example 1 is that the sulfonic acid group mass fraction in the resin containing sulfonic acid groups is 17.6%. The rest is the same as in Example 1.
[0077] Example 3 The difference between Example 3 and Example 1 is that the sulfonic acid group mass fraction in the resin containing sulfonic acid groups is 20.27%. The rest is the same as in Example 1.
[0078] Example 4 The difference between Example 4 and Example 1 is that the sulfonic acid group mass fraction in the resin containing sulfonic acid groups is 16%. The rest is the same as in Example 1.
[0079] Example 5 The difference between Example 5 and Example 1 is that the sulfonic acid group mass fraction in the resin containing sulfonic acid groups is 21%. The rest is the same as in Example 1.
[0080] Example 6 The difference between Example 6 and Example 1 is that the mass ratio of the resin containing sulfonic acid groups and the mesoporous molecular sieve is different; the resin containing sulfonic acid groups is 100 g, and the mesoporous molecular sieve is 2 g. Everything else is the same as in Example 1.
[0081] Example 7 The difference between Example 7 and Example 1 is that the mass ratio of the resin containing sulfonic acid groups and the mesoporous molecular sieve is different; the resin containing sulfonic acid groups is 20 g, and the mesoporous molecular sieve is 2 g. Everything else is the same as in Example 1.
[0082] Example 8 The difference between Example 8 and Example 1 is that the mass ratio of the resin containing sulfonic acid groups and the mesoporous molecular sieve is different; the resin containing sulfonic acid groups is 220g and the mesoporous molecular sieve is 2g. Everything else is the same as in Example 1.
[0083] Example 9 The difference between Example 9 and Example 1 is that the mass ratio of the resin containing sulfonic acid groups and the mesoporous molecular sieve is different; the resin containing sulfonic acid groups is 10g and the mesoporous molecular sieve is 2g. The rest is the same as in Example 1.
[0084] Example 10 The difference between Example 10 and Example 1 is that the melt mixing temperature is different in the composite resin preparation method; in Example 10, the melt mixing temperature is 160°C. Everything else is the same as in Example 1.
[0085] Example 11 The difference between Example 11 and Example 1 is that the melt mixing temperature is different in the composite resin preparation method; in Example 11, the melt mixing temperature is 230°C. Everything else is the same as in Example 1.
[0086] Example 12 The difference between Example 12 and Example 1 is that the melt mixing temperature is different in the composite resin preparation method; in Example 12, the melt mixing temperature is 150°C. Everything else is the same as in Example 1.
[0087] Example 13 The difference between Example 13 and Example 1 is that the melt mixing temperature is different in the composite resin preparation method; in Example 13, the melt mixing temperature is 240°C. Everything else is the same as in Example 1.
[0088] Example 14 The difference between Example 14 and Example 1 is that the mass ratio of the composite resin to ethanolamine is different in the modified resin preparation method, and the amount of ethanolamine added is 0.8 mol. Everything else is the same as in Example 1.
[0089] Example 15 The difference between Example 15 and Example 1 is that the mass ratio of the composite resin to ethanolamine is different in the modified resin preparation method, and the amount of ethanolamine added is 0.45 mol. Everything else is the same as in Example 1.
[0090] Example 16 The difference between Example 16 and Example 1 is that the mass ratio of the composite resin to ethanolamine is different in the modified resin preparation method, and the amount of ethanolamine added is 0.35 mol. The rest is the same as in Example 1.
[0091] Example 17 The difference between Example 17 and Example 1 is that the mass ratio of the composite resin to ethanolamine is different in the modified resin preparation method, and the amount of ethanolamine added is 0.9 mol. The rest is the same as in Example 1.
[0092] Example 18 The difference between Example 18 and Example 1 is that the type of alkanolamine organic compound used in the modified resin preparation method is different; otherwise, it is the same as in Example 1. The structural formula of the alkanolamine organic compound in Example 18 is as follows.
[0093] .
[0094] Example 19 The difference between Example 19 and Example 1 is that the type of alkanolamine organic compound used in the modified resin preparation method is different; otherwise, it is the same as in Example 1. The alkanolamine organic compound in Example 19 has structural formula 5.
[0095] Example 20 The difference between Example 20 and Example 1 is that the type of alkanolamine organic compound used in the modified resin preparation method is different; otherwise, it is the same as in Example 1. The alkanolamine organic compound in Example 20 has structural formula 4.
[0096] Example 21 The difference between Example 21 and Example 1 is that the type of alkanolamine organic compound used in the modified resin preparation method is different; otherwise, it is the same as in Example 1. The structural formula of the alkanolamine organic compound in Example 21 is as follows.
[0097] .
[0098] Example 22 The difference between Example 22 and Example 1 is that in the composite resin preparation method, the D50 particle size of the particles processed from the melt blend in Example 22 is 0.5 mm, and the D50 particle size of the prepared composite resin is also 0.5 mm. The rest is the same as in Example 1.
[0099] Example 23 The difference between Example 23 and Example 1 is that in the composite resin preparation method, the D50 particle size of the particles processed from the melt blend in Example 23 is 1.5 mm, and the D50 particle size of the prepared composite resin is also 1.5 mm. The rest is the same as in Example 1.
[0100] Example 24 The difference between Example 24 and Example 1 is that in the composite resin preparation method, the D50 particle size of the particles processed from the melt blend in Example 24 is 0.4 mm, and the D50 particle size of the prepared composite resin is also 0.4 mm. The rest is the same as in Example 1.
[0101] Example 25 The difference between Example 25 and Example 1 is that in the composite resin preparation method, the D50 particle size of the particles processed from the melt blend in Example 25 is 1.8 mm, and the D50 particle size of the prepared composite resin is also 1.8 mm. The rest is the same as in Example 1.
[0102] Example 26 Compared with Example 1, Example 26 first grafts an alcohol amine and then introduces a mesoporous molecular sieve. The specific steps are as follows.
[0103] Preparation of modified resin: 200 g of resin containing sulfonic acid groups and 0.5 mol ethanolamine (30.9 g) were added to a reaction vessel and stirred continuously at 100 °C for 4 h. After the reaction, the mixture was filtered, washed with water, and dried to obtain a modified resin with -OH and -SO3H groups on its surface. The modified resin was then subjected to post-treatment.
[0104] The post-treatment steps for the modified resin in Example 26 are the same as in Example 1.
[0105] The post-treated modified resin was packed into a column, and 2 g of mesoporous molecular sieve was added. After thorough mixing, 10 kg of ethylene glycol was used for column adsorption to remove impurities. After adsorption and impurity removal, the transmittance of ethylene glycol at all wavelengths increased. Specifically, the transmittance at 220 nm was 76.11%, with an average increase of 24%; the transmittance at 250 nm was 92.35%, with an average increase of 15.6%; and the transmittance at 275 nm was 97.94%, with an average increase of 4.17%.
[0106] Table 2 shows the UV transmittance data of ethylene glycol before and after adsorption at different wavelengths in Example 26.
[0107] Table 2 Comparative Example 1 Compared with Example 1, no mesoporous molecular sieve was introduced into the resin in Comparative Example 1; the specific steps are as follows.
[0108] 200 g of resin containing sulfonic acid groups and 0.5 mol of an alkanolamine organic compound were added to a reaction vessel and stirred continuously at 100 °C for 4 h. After the reaction, the mixture was filtered, washed with water, and dried to obtain a modified resin with a large number of -OH and -SO3H groups on its surface. The modified resin was then subjected to post-treatment.
[0109] The post-treatment steps for the modified resin in Comparative Example 1 are the same as in Example 1.
[0110] After the above-mentioned steps, the resin was directly packed into a column for adsorption and impurity removal of ethylene glycol. After adsorption and impurity removal, the transmittance of ethylene glycol at various wavelengths increased slightly, with a transmittance of 65.12% at 220 nm. The product did not meet the polyester-grade standard, resulting in an average increase in transmittance of approximately 13%. Polyester-grade ethylene glycol requires a transmittance >75% at 220 nm.
[0111] Table 3 shows the UV transmittance data of ethylene glycol before and after adsorption in Comparative Example 1 at different wavelengths.
[0112] Table 3 Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the resin used in the preparation of the composite resin does not contain sulfonic acid groups, while the rest is the same as in Example 1.
[0113] Comparative Example 3 Compared with Example 1, Comparative Example 3 uses a different post-treatment method for the modified resin, employing existing resin post-treatment methods; details are as follows. The preparation method of the modified resin in Comparative Example 3 is the same as in Example 1.
[0114] The post-treatment process of the resin in Comparative Example 3 is as follows: HCl and NaOH solutions with a mass fraction of 4%~5% were added sequentially to 200g of modified resin at a volume of 3 times that of the modified resin, and each solution was washed for 4 hours. Then, the resin was washed with pure water (12 times in total) until the conductivity of the solution was lower than 10μs / cm and the liquid was colorless and transparent. The resin was then dried.
[0115] The modified resin, after the above steps, was directly packed into a column for adsorption of ethylene glycol. The UV transmittance of ethylene glycol before and after adsorption (nitrogen purging, no dissolved oxygen) was measured in the adsorption experiment and is shown in Table 4 below.
[0116] Table 4 The UV transmittance of ethylene glycol before and after adsorption in Examples 1-26 and Comparative Examples 1-3 is shown in Table 5.
[0117] Table 5. UV transmittance of ethylene glycol at 220 nm and 275 nm before and after adsorption in each example and comparative example. Continued from Table 5 By comparing Examples 1 and 26 with Comparative Example 1, the modified resin preparation method in Example 26, which involves first grafting alkanolamines and then introducing mesoporous molecular sieves, resulted in a lower improvement in the UV transmittance of ethylene glycol at different wavelengths compared to Example 1. In Comparative Example 1, no mesoporous molecular sieves were added, and the UV transmittance of ethylene glycol at different wavelengths after impurity removal using the method in Comparative Example 1 was even lower than that in Example 26. A comparison of Examples 1, 26, and Comparative Example 1 suggests that if resins containing sulfonic acid groups are first grafted with alkanolamines before being introduced into mesoporous molecular sieves, the free hydroxyl groups in the mesoporous molecular sieves will affect the amount of alkanolamines introduced, reducing the adsorption effect on subsequent impurities. This indicates that using the ethylene glycol impurity removal method provided in this application, which involves first introducing resins containing sulfonic acid groups into molecular sieves and then grafting alkanolamines during modification, can improve the impurity removal and adsorption effect of ethylene glycol, significantly enhancing its UV transmittance.
[0118] Comparing Example 1 and Comparative Example 3, Comparative Example 3 used a traditional post-treatment method to treat the modified resin. After ethylene glycol adsorption for impurity removal, the transmittance of ethylene glycol in Comparative Example 3 decreased, and the transmittance decreased more significantly in each wavelength band as the contact time between ethylene glycol and resin increased. It is speculated that impurities introduced into the modified resin during the original production process were not effectively removed, leading to a significant decrease in the UV transmittance of ethylene glycol. This indicates that the resin activated using this method cannot be directly used to adsorb impurities affecting the transmittance of ethylene glycol. The comparison between Comparative Example 3 and Example 1 shows that using the post-treatment method provided in this application for the modified resin, with the first stirring and washing using pure water to remove soluble impurities introduced into the modified resin during the original production process, and the second stirring and washing using a first alcohol solution to remove organic impurities introduced into the modified resin during the original production process, helps to improve the UV transmittance of ethylene glycol.
[0119] Compared with Comparative Example 2, Example 1 did not contain sulfonic acid groups, and the UV transmittance remained essentially unchanged before and after ethylene glycol adsorption. This indicates that a modified resin containing sulfonic acid groups was used, and the sulfonic acid group H... + Under catalysis, aldehydes and carboxylic acid impurities in ethylene glycol undergo aldol condensation and esterification reactions with -OH groups in the modified resin, thereby removing aldehydes and carboxylic acid impurities from ethylene glycol.
[0120] A comparison of Examples 1-3 and Examples 4-5 shows that when the mass fraction of sulfonic acid groups in the resin containing sulfonic acid groups is in the range of 17.6% to 20.27%, using modified resin to remove impurities from ethylene glycol helps remove aldehydes and carboxylic acids, improving the UV transmittance of ethylene glycol. A comparison of Examples 1, 6-7, and Examples 8-9 shows that when the mass ratio of resin containing sulfonic acid groups to mesoporous molecular sieves is in the range of (10~100):1, using modified resin to remove impurities from ethylene glycol allows the mesoporous molecular sieves to rapidly adsorb the generated water, significantly reducing the reverse reaction caused by water accumulation, effectively preventing impurity desorption, and resulting in higher UV transmittance of ethylene glycol. A comparison of Examples 1, 10-11, and Examples 12-13 shows that in the composite resin preparation method, a melt mixing temperature in the range of 160~230℃ is beneficial for uniformly introducing mesoporous molecular sieves into the resin containing sulfonic acid groups, ensuring uniform distribution of the molecular sieves within the resin, improving impurity removal efficiency, and increasing the UV transmittance of ethylene glycol. A comparison of Examples 1, 14-15, and 16-17 illustrates that both excessive and insufficient content of alkanolamine organic compounds added in the modified resin preparation method affects the UV transmittance of ethylene glycol. When the mass ratio of composite resin to alkanolamine organic compounds is in the range of (4.1~8.2):1, appropriate modification of the composite resin with an appropriate amount of alkanolamine is beneficial for the removal of impurities from ethylene glycol, thus improving the UV transmittance of ethylene glycol. A comparison of Examples 1, 18-21 shows that as long as the added alkanolamine organic compounds satisfy the structural formulas 1-5, they all have the same impurity removal effect, improving the UV transmittance of ethylene glycol. A comparison of Examples 1, 22-23, and 24-25 shows that the particle size (D50) of the processed particles in the melt blend is in the range of 0.5~1.5 mm, which helps to improve the adsorption effect of the modified resin on macromolecular impurities in ethylene glycol, reduces the probability of interaction between impurities and hydroxyl groups in the modified resin, and improves the adsorption effect on impurities in ethylene glycol.
[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A modified resin, characterized in that, The modified resin is used for impurity removal from ethylene glycol and includes a composite resin and a modifier grafted onto the composite resin. The modifier includes an alkanolamine organic compound, and the composite resin contains sulfonic acid groups and mesoporous molecular sieves. Obtaining the composite resin includes the following steps: A resin containing sulfonic acid groups is mixed with a mesoporous molecular sieve to form a melt blend, and the melt blend is pretreated to obtain the composite resin. The total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 17.6%~20.27%. The mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve is (10~100):1; The process of mixing a resin containing sulfonic acid groups with a mesoporous molecular sieve to form a melt blend includes the following steps: The resin containing sulfonic acid groups and the mesoporous molecular sieve are added to a container and premixed by stirring, followed by melt mixing. The melt mixing temperature is 160~230℃ and the stirring time for melt mixing is ≥2h. The composite resin has a D50 particle size of 0.5~1.5mm; The mass ratio of the composite resin to the alkanolamine organic compound is (4.1~8.2):
1.
2. The modified resin according to claim 1, characterized in that, The alkanolamine organic compounds include one or more of the following structural formulas: Where 1≤n≤4, R1 is selected from -CH3 or -CH2-CH3.
3. A method for preparing the modified resin according to any one of claims 1-2, characterized in that, Includes the following steps: A composite resin containing sulfonic acid groups and mesoporous molecular sieves was obtained; The composite resin is mixed with the alkanolamine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups.
4. The method for preparing the modified resin according to claim 3, characterized in that, Obtaining a composite resin containing sulfonic acid groups and mesoporous molecular sieves includes the following steps: A resin containing sulfonic acid groups is mixed with a mesoporous molecular sieve to form a melt blend, and the melt blend is pretreated to obtain the composite resin.
5. The method for preparing the modified resin according to claim 4, characterized in that, The total mass of the resin containing sulfonic acid groups is 100%, and the mass content of the sulfonic acid groups is 17.6%~20.27%. The mass ratio of the resin containing sulfonic acid groups to the mesoporous molecular sieve is (10~100):
1.
6. The method for preparing the modified resin according to claim 3, characterized in that, The process of mixing a resin containing sulfonic acid groups with a mesoporous molecular sieve to form a melt blend includes the following steps: The resin containing sulfonic acid groups and the mesoporous molecular sieve are added to a container and premixed by stirring, followed by melt mixing. The melt mixing temperature is 160~230℃ and the stirring time is ≥2h.
7. The method for preparing the modified resin according to claim 3, characterized in that, The composite resin is obtained by pretreating the melt blend, including the following steps: The molten blend is compressed into tablets and cooled to obtain a composite resin. The preheating time of the press used for tableting is 10~30min, the pressure of tableting is 0.5~3.0MPa, and the melt compression temperature during tableting is 160~220℃. The D50 particle size of the composite resin is 0.5~1.5mm.
8. The method for preparing the modified resin according to claim 3, characterized in that, The composite resin is mixed with an alkanolamine organic compound and heated to obtain a modified resin containing -OH and -SO3H groups, comprising the following steps: A composite resin and an alcohol amine organic compound with a mass ratio of (4.1~8.2):1 are added to a container, heated and stirred at a temperature of 60~100℃ for ≥4h. After that, the mixture is filtered, washed with water, and dried to obtain a modified resin containing -OH and -SO3H groups.
9. A method for removing impurities from ethylene glycol, characterized in that, The modified resin includes the modified resin prepared by the preparation method of the modified resin according to any one of claims 1-2 or any one of claims 3-8; The ethylene glycol impurity removal method includes the following steps: The modified resin is then post-treated. The post-treatment includes washing the modified resin with an alcohol solution; The post-treated modified resin was packed into a column, and impurities were removed by passing it through the column with ethylene glycol.
10. The method for removing impurities from ethylene glycol according to claim 9, characterized in that, The modified resin is then post-treated, including the following steps: The modified resin and pure water are mixed to obtain a first solution. The first solution is stirred and washed for the first time. The pure water is replaced during the first stirring and washing process. The first stirring and washing is completed when the first solution is colorless and transparent and has a conductivity of <10μs / cm. The amount of pure water added is 2 to 3 times the volume of the modified resin, and the first stirring and washing time is 0.5 to 4 hours. The pure water is replaced when the transmittance of the first solution at 220 nm does not decrease. After the first stirring and cleaning is completed, the modified resin is washed with an alcohol solution, including the following steps: mixing the modified resin and the first alcohol solution to obtain a second solution, stirring and cleaning the second solution a second time, replacing the first alcohol solution during the second stirring and cleaning process, and stirring and cleaning the second solution until the transmittance of the second solution at 220 nm is >10%, at which point the second stirring and cleaning is completed. The amount of the first alcohol solution added is 2 to 3 times the volume of the modified resin, and the second stirring and washing time is 2 to 4 hours. The first alcohol solution is replaced when the transmittance of the second solution at 220 nm does not decrease. The modified resin after post-treatment is packed into a column, and the ethylene glycol column impurity removal includes the following steps: after the second stirring and washing, the modified resin after the second stirring and washing is transferred to the adsorption column, and the second alcohol solution is continuously passed through the adsorption column dynamically until the transmittance of the second alcohol solution at 220 nm is higher than 50%, and the modified resin is dried.
Citation Information
Patent Citations
Adsorbent for purifying coal ethylene glycol and preparation method of adsorbent for purifying coal ethylene glycol
CN104275157A
Preparation for glycol dealdehyding adsorbing agent
CN105457610A